Antibacterial and Antioxidant Activities of Cutibacterium acnes on Jatropha gossypifolia leaves and Pommetia pinata Bark - Zahra, Ummi; Nur, Arfiani; Kurniati, Nunung; Yusril, Yusril; Baharuddin, Maswati (Chimica et Natura Acta, 2025)
Cutibacterium acnes is a bacterium that can cause inflammation of the skin tissue and lead to acne. Inhibitory activity treatment can be carried out using natural compounds unique to Indonesia as a tropical country, namely Pometia pinnata stem bark and red Jatropha gossypifolia leaves. Pometia pinnata stem bark and red Jatropha gossypifolia leaves are known to have the potential for antibacterial activity. This study aims to combine the two plants as anti-bacterial agents against Cutibacterium acnes and as antioxidants. The method used in this study was maceration, employing ethanol and ethyl acetate solvents for antibacterial and antioxidant activity tests, specifically paper disc diffusion and DPPH assays. The results showed that J. gossypifolia and Pometia pinnata leaf extracts contain flavonoids, steroids, terpenoids, alkaloids, and tannins. The antibacterial activity of a mixture of ethanol extracts from J. gossypifolia and Pometia pinnata leaves against Cutibacterium acnes bacteria was strong, categorized at a concentration of 25%. Additionally, there was no significant difference in the antioxidant capacity between the mixture of ethanol and ethyl acetate extracts. The antioxidant capacity value was approximately 53% AEAC at a concentration of 500 ppm.